2020
DOI: 10.1002/fam.2863
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a ventilated‐façade system under fire conditions: An experimental investigation

Abstract: Summary During a fire event, ventilated facade systems may contribute to external fire spreading to the upper floors of a building via the facade, thus representing a significant risk. In this frame, the performance of a typical ventilated façade system under fire conditions is experimentally investigated, using a full‐scale compartment‐facade test rig. Two alternative façade configurations are examined and comparatively assessed, namely a plain façade (PF) and a ventilated façade (VF) system. Emphasis is give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…More than 22 years ago, a team of scientists and engineers by the National Institute of Standards and Technology (NIST) of the United States of America, in collaboration with the Technical Research Centre (TRC) of Finland, developed a powerful computer program to answer critical questions about the safety of buildings against fire. It may not be the only fire modeling simulator, but it remains the most advanced [20], [21].…”
Section: Fds Computational Fluid Dynamics Codementioning
confidence: 99%
See 1 more Smart Citation
“…More than 22 years ago, a team of scientists and engineers by the National Institute of Standards and Technology (NIST) of the United States of America, in collaboration with the Technical Research Centre (TRC) of Finland, developed a powerful computer program to answer critical questions about the safety of buildings against fire. It may not be the only fire modeling simulator, but it remains the most advanced [20], [21].…”
Section: Fds Computational Fluid Dynamics Codementioning
confidence: 99%
“…Arrangements (c) and (d) are prohibited. Display (e) is also permitted; however, its effects are controversial, and it is advisable to avoid it [21].…”
Section: Space Modelingmentioning
confidence: 99%
“…However, in most of the studies, significant idealization of fire scenarios and system configurations was done, and thus, future tests must consider more realistic fire conditions and the actual system configurations as much as possible. A fire within a room is more likely to enter the cavity through the perimeter of a window opening [3,7,39] for rainscreen façades, while the fire enters through inner glass pane cracking for double-skin façades [14,40]. The studies on external fire scenarios consider the combustion of cladding material as the path for the fire to enter the cavity.…”
Section: Fire Safety Risks Vs Cavity Typementioning
confidence: 99%
“…For a scenario where fire enters the cavity due to flame ejecting through a window opening of a rainscreen façade cavity arrangement, larger cavity widths and large fire sizes allow more flame to enter the cavity, which increases the risk [3,7,39]. Sultan [15] identified a risk of fire/flame spreading into upper levels through double-stud wall-floor joints for a fire scenario on the floor below the joint and found that when the cavity is narrower than 25 mm in width, it has less chance of fire penetrating the cavity.…”
Section: Fire Entering Upper and Adjacent Compartmentsmentioning
confidence: 99%
See 1 more Smart Citation